If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + -2g = 5 + 8g Solving -35 + -2g = 5 + 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. -35 + -2g + -8g = 5 + 8g + -8g Combine like terms: -2g + -8g = -10g -35 + -10g = 5 + 8g + -8g Combine like terms: 8g + -8g = 0 -35 + -10g = 5 + 0 -35 + -10g = 5 Add '35' to each side of the equation. -35 + 35 + -10g = 5 + 35 Combine like terms: -35 + 35 = 0 0 + -10g = 5 + 35 -10g = 5 + 35 Combine like terms: 5 + 35 = 40 -10g = 40 Divide each side by '-10'. g = -4 Simplifying g = -4
| 2x+17-1.2x=10-0.2x+11 | | 9y-9x=27 | | 2x+125+38=163 | | X-20.52=-2.09 | | 8+-x=2x+-1 | | 17-7=-3y+6y | | -2+-12x=58 | | 2y-6+3y-8= | | -12+2x=3x | | 8.9=2.1-1.3y | | 2x+125+38=168 | | -2+-12x=-58 | | 4m-3=2m+9 | | 9x^2-12x-96=0 | | .66x-11=x+4 | | 5x+6=3x+4 | | 2(3x-3.9)=4x-7.8 | | 14+X=16 | | (4+8i)-(9+4i)= | | Z-8z(1+4)=15 | | -2+-12x=-50 | | k+1=27 | | 9x-4=8x-6 | | 4.2+0.9x=0.6 | | (x+y)(2x^2-3xy+2y^2)= | | 9x+5-4=3x+6 | | -2+-12x=50 | | y^2=x+13 | | 16.1-2.8x=x+1.5 | | y+4.1=15.1 | | 3(x+2.19)=2x | | -27=-3w |